Prevalence, risk factors, and cardiovascular disease outcomes associated with persistent blood pressure control: The Jackson Heart Study. - Gabriel S Tajeu; Calvin L Colvin; Shakia T Hardy; Adam P Bress; Bamba Gaye; Byron C Jaeger; Gbenga Ogedegbe; Swati Sakhuja; Mario Sims; Daichi Shimbo; Emily C O'Brien; Tanya M Spruill; et al. (PLoS ONE)
Background Maintaining blood pressure (BP) control over time may contribute to lower risk for cardiovascular disease (CVD) among individuals who are taking antihypertensive medication. Methods The Jackson Heart Study (JHS) enrolled 5,306 African-American adults ≥21 years of age and was used to determine the proportion of African Americans that maintain persistent BP control, identify factors associated with persistent BP control, and determine the association of persistent BP control with CVD events. This analysis included 1,604 participants who were taking antihypertensive medication at Visit 1 and had BP data at Visits 1 (2000-2004), 2 (2005-2008), and 3 (2009-2013). Persistent BP control was defined as systolic BP <140 mm Hg and diastolic BP <90 mm Hg at all three visits. CVD events were assessed from Visit 3 through December 31, 2016. Hazard ratios (HR) for the association of persistent BP control with CVD outcomes were adjusted for age, sex, systolic BP, smoking, diabetes, and total and high-density lipoprotein cholesterol at Visit 3. Results At Visit 1, 1,226 of 1,604 participants (76.4%) with hypertension had controlled BP. Overall, 48.9% of participants taking antihypertensive medication at Visit 1 had persistent BP control. After multivariable adjustment for demographic, socioeconomic, clinical, behavioral, and psychosocial factors, and access-to-care, participants were more likely to have persistent BP control if they were <65 years of age, women, had family income ≥$25,000 at each visit, and visited a health professional in the year prior to each visit. The multivariable adjusted HR (95% confidence interval) comparing participants with versus without persistent BP control was 0.71 (0.46-1.10) for CVD, 0.68 (0.34-1.34) for coronary heart disease, 0.65 (0.27-1.52) for stroke, and 0.55 (0.33-0.90) for heart failure. Conclusion Less than half of JHS participants taking antihypertensive medication had persistent BP control, putting them at increased risk for heart failure.